1997
DOI: 10.1128/aac.41.3.575
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of voriconazole (UK-109,496) against fluconazole-susceptible and -resistant Candida albicans isolates from oral cavities of patients with human immunodeficiency virus infection

Abstract: The susceptibility of Candida albicans to a new antifungal triazole, voriconazole (UK-109,496), was investigated in 105 isolates obtained from the oral cavities of patients with human immunodeficiency virus (HIV) infection to study this drug's activity against fluconazole-susceptible and -resistant isolates. MICs were determined by a broth microdilution technique according to document M27-T from the National Committee for Clinical Laboratory Standards and by using a broth microdilution technique and a syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 11 publications
7
51
0
3
Order By: Relevance
“…It was notably more potent against C. krusei and C. glabrata than fluconazole and showed similar MICs to itraconazole for most susceptible isolates. This is consistent with published data for various isolate collections [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and clinical cases [7,[18][19][20][21]23].…”
Section: Discussionsupporting
confidence: 93%
“…It was notably more potent against C. krusei and C. glabrata than fluconazole and showed similar MICs to itraconazole for most susceptible isolates. This is consistent with published data for various isolate collections [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and clinical cases [7,[18][19][20][21]23].…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies have indicated that voriconazole has good activity against fluconazole-resistant isolates of C. glabrata and C. albicans [16,38], voriconazole MICs have been found to be proportionally higher against these isolates [13,16,38]. Although resistance to voriconazole has not been widely reported, it is nevertheless important to monitor voriconazole MICs closely, particularly if this azole antifungal is used widely as empirical therapy and in the treatment of invasive fungal infections.…”
Section: Discussionmentioning
confidence: 97%
“…The quality control strains were C. parapsilosis ATCC 22019 and C. krusei ATCC 6258 [5,6], and the reference strains were C. albicans ATCC 90028 and Paecilomyces variotii ATCC 22391 [12,16]. The permitted range of MICs for these strains is shown in Table 1.…”
Section: Isolatesmentioning
confidence: 99%
“…A number of clinical reports about voriconazole pharmacokinetics have been published [2][3][4][5][6][7][8][9][10][11], as well as numerous data obtained in in vitro investigations on the pharmacokinetic properties and activity of voriconazole [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%